2021
DOI: 10.2217/fon-2020-1262
|View full text |Cite
|
Sign up to set email alerts
|

Race and Ethnicity Representation in Clinical Trials: Findings from a Literature Review of Phase I Oncology Trials

Abstract: Aim: To provide an assessment of published literature on the demographic representation in Phase I trials of biopharmaceutical oncology agents. Materials & methods: We conducted a rapid evidence assessment to identify demographic representation reported in Phase I clinical trials for biopharmaceutical oncology agents published in 2019. Results: Globally, the population was predominantly White/Caucasian (62.2%). In the USA, the distribution was heavily skewed toward White/Caucasian (84.2%), with minimal rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
(20 reference statements)
2
24
1
Order By: Relevance
“…We were unable to perform analysis on sexual partner histories or socioeconomic status, as too few studies reported these variables. HPV-associated OPSCC differs drastically from other cancers in its incidence amongst Caucasians relative to non-Caucasians; whereas Camidge et al reported that African American men are more likely to have malignant tumors and lower rates of survival than the general population, Pytynia et al found that the stark preponderance of HPV-associated OPSCC in Caucasian males over the general population actually contributes to the diminishment in cancer-related disparities between Caucasian and African American males [ 44 , 48 ]. Although Kennedy-Martin et al found that RCT participant populations are highly selective and have lower risk profiles than that of the general population, they did so in the context of cardiology, mental health, and general oncology [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to perform analysis on sexual partner histories or socioeconomic status, as too few studies reported these variables. HPV-associated OPSCC differs drastically from other cancers in its incidence amongst Caucasians relative to non-Caucasians; whereas Camidge et al reported that African American men are more likely to have malignant tumors and lower rates of survival than the general population, Pytynia et al found that the stark preponderance of HPV-associated OPSCC in Caucasian males over the general population actually contributes to the diminishment in cancer-related disparities between Caucasian and African American males [ 44 , 48 ]. Although Kennedy-Martin et al found that RCT participant populations are highly selective and have lower risk profiles than that of the general population, they did so in the context of cardiology, mental health, and general oncology [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gender and phase 1 clinical study enrollment trends should be taken into consideration to provide a better insight into gender equity and accessibility to innovative therapeutic agents for the general population, as well as for children and the elderly, which will surely benefit from new commercialized drugs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, an analysis of global phase-1 trials of biopharmaceutical oncology agents showed that 62% of the participants were White. In the USA, 82.4% of the population was White, 7.3% were AAs, 3.4% were Asians, and 2.8% were Hispanic/Latinos and other races [ 70 ]. The underrepresentation of marginalized populations may undermine the generalizability of the trial findings and mask the heterogeneity of outcomes adverse events.…”
Section: Opportunities For Improvementmentioning
confidence: 99%